2011
DOI: 10.1017/s1368980011003041
|View full text |Cite
|
Sign up to set email alerts
|

Feedback in web-based questionnaires as incentive to increase compliance in studies on lifestyle factors

Abstract: Objective: We explored the use of feedback in interactive web-based questionnaires for collecting data on lifestyle factors in epidemiological studies. Design: Here we report from a cohort study on lifestyle factors and upper respiratory tract infections among 1805 men and women. We introduced interactivity in the form of personalized feedback and feedback on a group level regarding dietary intake, physical activity and incidence of infections in webbased questionnaires as incentives for the respondents to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…Marcus, Bosnjak, Lindner, Pilischenko, and Schütz (2007) find that for individuals who are not especially interested in the survey topic, personalized feedback provided after an initial web survey increases response rates in follow-up online surveys. This is in line with Bälter, Fondell, and Bälter (2011), who observed higher response rates in follow-up surveys for respondents provided with personalized feedback on responses regarding energy expenditure during the first interview.…”
Section: Background and State Of Researchsupporting
confidence: 89%
“…Marcus, Bosnjak, Lindner, Pilischenko, and Schütz (2007) find that for individuals who are not especially interested in the survey topic, personalized feedback provided after an initial web survey increases response rates in follow-up online surveys. This is in line with Bälter, Fondell, and Bälter (2011), who observed higher response rates in follow-up surveys for respondents provided with personalized feedback on responses regarding energy expenditure during the first interview.…”
Section: Background and State Of Researchsupporting
confidence: 89%
“…However, the response rate for rating the page content was very low and may be due to the fact that the page rating did not provide the users with feedback as was done in the questionnaire. A recent study explored using personalized feedback as incentive to increase compliance in Web-based questionnaires [38]. In addition, the variation in the rating responses may be due to the design of the rating process, as we have included the rating of each information page at the end of it.…”
Section: Discussionmentioning
confidence: 99%
“…Incentives may improve response rates, but may have to have considerable value before having an impact [25]. Providing feedback on questionnaires may improve response rates [26]. There has also been some work characterizing participants who are more likely to drop out from studies, with better response rates reported for people who are white, older, better educated, with good Internet skills [27-31].…”
Section: Introductionmentioning
confidence: 99%